Cognitive and psychopathologycal profile associated with antisocial behavior - Cifuentes Gonzalez, John Jairo (Editorial Bonaventuriana, 2018)
The objective of this study was to establish the components of the cognitive and psychopathological profile that characterize individuals judicially condemned, discriminating diagnosis of antisocial personality disorder (TPA). Participated 607 people which were divided into two groups: 398 cases (whith TPA) and 209 controls (without TPA). Instruments: YSQ-L (Young & Brown, 1999), validated by Castrillon et al. (2005), EEC-M (Londoño et al, 2006), the MCMI-II (Millon, 1999) and MINI (Scheehan and Lecrubier, 1999). Results: Variables associated with antisocial behavior were self-sufficient schemes of self-discipline, right grandeur and emotional privation, cognitive avoidance strategies, and religion, paranoid personality, schizoid, and compulsive and delusional clinical syndrome. A discriminant function was reported at a rate of 58,3% correct prediction of the classification for the group with TAP cognitive profile with an aggressive reaction (0,680) and cognitive avoidance (0,576).